Provincial Tax Performance in Indonesia and Determinants of Tax Revenue - Kurniawan, Dedi; Çevik, Savaş; Alagöz, Ali (Journal of Applied Accounting and Taxation, 2025)
This research seeks to assess the efficacy of tax revenues across 34 provinces in Indonesia and analyze the determinants affecting provincial tax collections on a national scale.  This research utilizes yearly data released by the Central Statistics Agency of Indonesia from 2019 to 2023.  The Tax Performance Index assesses tax revenue performance over a five-year period, using panel data regression analysis to evaluate the impact of various factors.  A panel data regression analysis was performed using the fixed effects model. The results of the regression analysis indicate that most provinces have not yet achieved optimal tax revenue levels.  The regression study findings indicate that Gross Domestic Product (GDP) per capita, Human Development Index, Percentage of Workforce, and Gini Index strongly influence tax revenues, both individually and together.  The research findings suggest that the government must consider both non-economic and economic factors that may influence tax collections.